Diospyros melanoxylon Roxb.: Quantitative Morphology of Leaf forms - Rathore, J. S. (Indian Forester, 1976)
This paper describes the quantitative morpholgy of four leaf forms found in D. melanoxylon Roxb., a dioecious and deciduous tree of India. Morphological characters such as leaf length, lamins apex and base angles, epidermal hairs, palisade cella, stomatal number and index and vein islet number are quantitatively described and analysed. Much confusion prevails in Indian flora records about the limitations of three species - D. melanoxylon, D. tomentosa and D. tupru - which were difrerentiated on the basis of leaf shape. The present study defines the four basic leaf shapes found in D. melanoxylon quantitatively and also gives insights into a complex morphological situation prevailing in this interesting endemic plant of India.